The manufacturing wage inequality in Latin America and East Asia: Openness, technology transfer, and labor supply - Avalos, Antonio; Savvides, Andreas (My University, 2006)
This paper examines wage inequality in the manufacturing sector for a panel of Latin American and East Asian economies during the last three decades. A labor supply and demand model is presented where three main determinants of wage inequality are investigated: trade openness, technology transfer, and labor supply. Findings indicate that wage inequality in the two regions has responded differently to the various determinants enumerated above. Some lessons from the comparative experience of the two regions are drawn.
Keywords: labor supply; manufacturing; technology transfer; wage